MHD Natural Convection and Entropy Generation in a Nanofluid-Filled Cavity With a Conductive Partition - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Elsevier Inc., 2018)
Magneto-hydrodynamic (MHD) free convection in a partitioned enclosure filled with various nanofluids (alumina-water and copper-oxide-water) on different parts of a cavity was examined numerically using the finite element method. The vertical walls of the cavity were kept at isothermal hot and cold temperatures while other walls were kept adiabatic. Various combinations of Hartmann numbers were used for the left and right half cavities filled with different nanofluids. Numerical simulations were performed for different values of Grashof numbers, thermal conductivity ratios, Hartmann numbers, and solid volume fractions of the nanofluid. It was observed that the average heat transfer rate increased with the Grashof number, thermal conductivity ratio, and solid nanoparticle volume fraction, whereas it deteriorated with the magnetic field. An entropy generation analysis of systems for various parameter combinations was also performed. © 2018 Elsevier Inc. All rights reserved.
Keywords: Finite element method; MHD convection; Nanofluids; Partition